The biotechnological potential of bacterial extracellular polymeric substances in lead biosorption - Maumela, Pfariso; Serepa-Dlamini, Mahloro (Frontiers in Microbiology, 2025)
IntroductionExtracellular polymeric substances are composed of a diverse range of functional groups, thereby making a strong case for their consideration as biosorbents in heavy metal bioremediation. This study, therefore, assessed strategies to enhance the biotechnological potential of extracellular polymeric substances produced by an endophytic bacterium, Bacillus MHSD_36.MethodsDesign of experiments were used to optimize the yield of extracellular polymeric substances from Bacillus MHSD_36. A mixture design was subsequently used to develop a cocktail of EPS and hydrophobicity components for the optimal biosorption of lead.ResultsThe production of the EPS, from MHSD_36, was optimized through lead induction at a concentration and time of 5.23 mg/L and 10.75 h, respectively. The optimum yield was 1.65 g/L EPS. The use of garden compost, as an alternative growth medium, was sufficient to give an EPS yield (1.15 g/L) comparable to sucrose based medium (1.25 g/L) under optimal induction conditions. The EPS from the Bacillus MHSD_36 had a Pb biosorption of 14.24%. However, a mixture of EPS with the hydrophobicity components significantly enhanced the Pb biosorption. The optimal proportion for the mixture was estimated to be 0.25 and 0.75, respectively with a maximum Pb biosorption of 95.8%. The acid recovery of EPS after the biosorption was effective to recover and recycle EPS in heavy metal biosorption.DiscussionThe production of EPS using garden compost and the subsequent recovery after biosorption of heavy metal offers a sustainable approach for the biotechnological application of bacterial EPS in environmental bioremediation.